2015
DOI: 10.17796/1053-4628-39.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Lysozyme in Relation to Dental Caries among Thai Preschoolers

Abstract: The up-regulated expression of salivary lysozyme and the increased lysozyme activity in S-ECC preschoolers suggests a possible connection between salivary lysozyme and oral immunity in response to early childhood dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Chereda (2012) suggests that there is a misbalance between the microbial load and local immunity reflected in changes of biofilm followed by shifting of the hydrogen index to the acid side and increases demineralization of the hard dental tissues. The obtained data regarding the reduction of lysozyme activity in case of caries progression is confirmed by other sources and can be used in the diagnosis of this disease (Lertsirivorakul et al 2015;Lertsirivorakul et al 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Chereda (2012) suggests that there is a misbalance between the microbial load and local immunity reflected in changes of biofilm followed by shifting of the hydrogen index to the acid side and increases demineralization of the hard dental tissues. The obtained data regarding the reduction of lysozyme activity in case of caries progression is confirmed by other sources and can be used in the diagnosis of this disease (Lertsirivorakul et al 2015;Lertsirivorakul et al 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, Letsirivorakul et.al. [49] obtained similar results, unstimulated saliva sample taken from 32 caries-free children and 32 children with caries showed the concentration and lysozyme activity in children with caries were higher than in caries-free children (p = 0.008). Different results reported by Felizardo et.al [50] that found lysozyme unrelated to the caries experience.…”
Section: Advances In Health Science Research Volumesupporting
confidence: 62%
“…Thanks to the biological activity of lysozyme, the formation of biofilms by cariogenic bacteria and the adhesion of Streptococcus mutans to hydroxyapatite are reduced [28]. According to the available literature, studies were conducted to determine whether there is a relationship between the level of lysozyme and the activity of caries [49,50]. Jentsch et al, in a study of adults followed for caries over a period of 4 years, observed that a lower caries increment was associated with lower levels of lysozyme [49].…”
Section: Discussionmentioning
confidence: 99%